Determination of Abraham model solute descriptors for monomeric 3, 4, 5-trimethoxybenzoic acid from experimental solubility data in organic solvents measured at 298.2 K. (4th May 2018) - Hart, Erin; Klein, Alex; Zha, Olivia; Wadawadigi, Anisha; Qian, Ellen; Dunn, Sarah; Herron, Janna; Kankolongo, Ketsia; Ryan, Shy'an; Acree, William E.; Abraham, Michael H.
ABSTRACT: Spectroscopic methods are employed to determine the experimental solubility of 3, 4, 5-trimethoxybenzoic acid dissolved in propylene carbonate, in 19 alcohol, in 4 alkyl ether, in 5 alkyl alkanoate and in 4 alkoxyalcohol solvents at 298.2 K. 3, 4, 5-Trimethoxybenzoic acid is believed to exist predominantly in monomeric form in each of the 34 organic solvents studied. The measured solubilities in 29 of the organic solvents are used to calculate the Abraham model solute descriptors for the monomeric form of 3, 4, 5-trimethoxybenzoic acid. Solubilities in the remaining five solvents could not be used in the solute descriptor computations because Abraham model equation coefficients are not available for these solvents. The derived solute descriptors back-calculated the observed solubility data to within 0.10 log units.